A Train-the-Trainer Programme to Deliver High Quality Education for Healthcare Providers - Peck, Jessica (Anti-Trafficking Review, 2021)
A promising practice for educating anti-trafficking stakeholders in healthcare emerged through an innovative train-the-trainer programme from a National Association of Pediatric Nurse Practitioner’s initiative called the Alliance for Children in Trafficking (ACT). The purpose of this training is to provide effective, high-quality education development with wide dissemination and reach. The obstacles to in-person education due to COVID-19 resulted in a pivot to a virtual platform to continue the ACT Advocate programme. This paper considers the engagement of the nursing profession in operationalising the ACT Advocate programme as a way to lead advocacy and education efforts, using a public health approach, for effective responses to child trafficking.